2010
DOI: 10.1159/000320988
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mild Cognitive Impairment and Its Subtypes in the Heinz Nixdorf Recall Study Cohort

Abstract: Aims: We investigated the prevalence of mild cognitive impairment (MCI) and its subtypes according to the original (MCI-original) and modified (MCI-modified; neglecting cognitive complaints) Petersen criteria. Methods: 4,145 subjects (aged 50–80 years) from a German population-based study completed a cognitive screening test and were poststratified into 2 groups with sample sizes of 1,125 for impaired and 3,020 for age-appropriate performance. Random samples of 445 impaired participants and 211 age-appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 99 publications
0
26
1
1
Order By: Relevance
“…The cognitive performance assessment has been previously described in detail (Wege et al 2011; Dlugaj et al 2010). Briefly, it consists of established measures of immediate and delayed verbal memory (eight-word list, performance measured as number of words recalled in each trial), problem solving/speed of processing (labyrinth test, time in seconds needed to complete the task), verbal fluency (semantic category “animals,” number of recalled words within 1 min) and abstraction (as an executive function)/visual–spatial organization (clock-drawing test).…”
Section: Methodsmentioning
confidence: 99%
“…The cognitive performance assessment has been previously described in detail (Wege et al 2011; Dlugaj et al 2010). Briefly, it consists of established measures of immediate and delayed verbal memory (eight-word list, performance measured as number of words recalled in each trial), problem solving/speed of processing (labyrinth test, time in seconds needed to complete the task), verbal fluency (semantic category “animals,” number of recalled words within 1 min) and abstraction (as an executive function)/visual–spatial organization (clock-drawing test).…”
Section: Methodsmentioning
confidence: 99%
“…There is a general consensus that the former is related with AD, whereas the latter is believed to reflect the prodromal stage of vascular, frontotemporal, or Lewy Body dementia [13,14]. The few studies examining this relationship have mostly been of cross-sectional design [15,16,17,18], and longitudinal data is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Third, disease progression varies from slow to intermediate to rapid [12]. Moreover, MCI is not a homogeneous pathology and is currently described as two clinical conditions - with amnestic symptoms (aMCI) and without amnestic symptoms [8,13]. Some publications have reported that aMCI converts to dementia more frequently [14,15].…”
Section: Introductionmentioning
confidence: 99%